Komunikasi Interpersonal dan Kinerja Usaha Kecil Menengah di Palangka Raya; Berbagi Pengetahuan sebagai Mediasi (Jurnal Manajemen Sains dan Organisasi, 2020)
Purpose, - This research aims to provide empirical explanation on the influence of interpesonal communication on UMKM performance with knowledge sharing as intervening.Design/methodology/approach - The research method used is descriptive-quantitative. This research analysis Unit is a staff of 139 people with census sample techniques or total sampling. The collected Data is analyzed using a Structural Equation Modelling (SEM) approach. The Software used is SmartPLS 3.2.8. Findings - The results showed that the influence of interpesonal communication has positive and significant impact on umkm performance, the influence of interpesonal communication is positive and significant impact on knowledge sharing, influential knowledge sharing Positive and significant to umkm performance, knowledge sharing intervening the influence of interpesonal communication towards umkm performance